“TO THE OTHER WORLD WITH OWN SUPPLIES”: VISUAL SYMBOLS ON MUSLIM FUNERARY MONUMENTS IN EURASIA AND THE CAUCASUS - Babadzanov, Bahtiar Miraimovic; Mederova, Dina Esirkepovna (History, Archeology and Ethnography of the Caucasus, 2025)
A distinctive feature of funerary monuments at Muslim shrines in Eurasia and the Caucasus is the prevalence of imagery depicting weapons, tools, and household items on tombstones and within mausoleums. Zoomorphic motifs, including totem animals, and, less frequently, anthropomorphic images, often appear in the decoration of these structures. The interiors of Kazakh mausoleums are adorned with similar iconography. Existing scholarship often limits analysis to formal descriptions of these images or cursory interpretations linking them to the deceased’s profession or invoking their “ancient roots” through historical and ethnographic comparisons. Such approaches are narrowly focused and leave broader anthropological questions underexplored. This study examines a selection of artifacts, including previously unpublished examples, and proposes a reinterpretation of the imagery on these grave structures. We view them as expressions of material culture that embody the societal imagination and ideological frameworks of their creators, who evidently perceived no religious prohibitions against such decorations. By adopting a broader anthropological perspective, this article considers these images not merely as ethnographic artifacts but as a form of “non-written reading” that reveals the religious practices, beliefs, and cultural ideologies of the communities that produced them.